Ceramic-based aerogel and preparation method thereof

The problem of limited application range of existing aerogels in low and high temperature fields is solved by using alumina flexible fibers and porous powders, and excellent thermal insulation and fire resistance under two temperature conditions are achieved.

CN119841615AActive Publication Date: 2025-04-18ANYI TAOJI NEW MATERIAL TECH (ZIBO) CO LTD +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510330191.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-20
Publication Date
2025-04-18
Estimated Expiration
2045-03-20

AI Technical Summary

Technical Problem

The application range of existing aerogels in low temperature and high temperature fields is limited. Ceramic aerogels have high thermal conductivity, poor thermal insulation performance, poor rigidity and high brittleness in the low temperature field.

Method used

Alumina flexible fibers and porous powders are used as the main raw materials to synthesize fiber gels by in-situ generation method and ceramicized in aqueous silica solution. Combined with a surface treatment agent and a light-shielding solvent, a ceramic-based aerogel with high flexibility and low thermal conductivity is formed.

Benefits of technology

Ceramic-based aerogel has an thermal insulation effect comparable to glass fiber aerogel in the low temperature field, and is better insulated than ceramic aerogel in the high temperature field, with excellent fire-proof and thermal insulation performance and good waterproofing ability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119841615A_ABST
    Figure CN119841615A_ABST
Patent Text Reader

Abstract

The invention provides a ceramic-based aerogel and a preparation method thereof, and belongs to the technical field of aerogel materials. According to the ceramic-based aerogel, aluminum oxide flexible fibers with a hollow structure and good flexibility and porous powder are used as main raw materials, fiber gel can be generated in situ under the action of a catalyst, the flexibility of the ceramic-based aerogel is improved, the heat conductivity coefficient is greatly reduced, and the ceramic-based aerogel has a good heat absorption effect and excellent fireproof heat insulation performance; good heat insulation effects are achieved in the low-temperature field and the high-temperature field. The mechanical strength and flexibility of the ceramic-based aerogel can be enhanced through the synergistic effect of the aluminum oxide flexible fibers and the silicon dioxide aqueous solution, and the mechanical capacity is improved. The use of the surface treating agent enables the ceramic-based aerogel to have good waterproof ability, and the synergistic effect of the alumina flexible fibers with low heat conductivity coefficient and the shading solvent enables the ceramic-based aerogel to have better heat absorption effect and excellent fireproof and heat-insulating performance. The preparation method is simple in process, low in cost and suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aerogel materials and relates to a ceramic-based aerogel and a preparation method thereof. Background Art

[0002] With the development of new energy vehicles, battery safety has become a focus of attention, and how to extend the escape time after battery failure has become a top priority. Aerogel has the characteristics of high specific surface area and porosity, low density, low thermal conductivity, and good thermal insulation performance. It has been used by most car companies in recent years; at the same time, it has also become a research hotspot in various high-temperature engineering systems such as industrial building insulation, aerospace, and nuclear power.

[0003] Aerogel is a porous material with a three-dimensional network structure composed of nano-skeleton and nano-pores, which is mainly divided into glass fiber aerogel and ceramic aerogel. Glass fiber aerogel is a composite material based on aerogel and combined with glass fiber. It has good thermal insulation, fire resistance and waterproof properties. However, glass fiber aerogel is mainly used in low-temperature fields due to its poor temperature resistance and cannot be used in high-temperature fields. Ceramic aerogel is a nano-scale porous solid material prepared by the sol-gel method. It has low density and thermal conductivity, good thermal insulation, good hydrophobicity and air permeability. However, ceramic aerogel has problems such as high thermal conductivity, poor thermal insulation, poor rigidity and high brittleness in low-temperature fields, so it is mainly used in high-temperature fields.

[0004] Therefore, there is a need for an aerogel that can be used both in low-temperature fields and in high-temperature fields to expand the application range of aerogels. Summary of the invention

[0005] The purpose of the present invention is to provide a ceramic-based aerogel and a preparation method thereof, so as to solve the problem that the application range of existing aerogels is limited.

[0006] To achieve the above object, the present invention adopts the following technical solutions: The present application provides a ceramic-based aerogel, the preparation raw materials of which include: flexible aluminum oxide fibers, porous powder, sol, cross-linking agent, catalyst, silicon dioxide aqueous solution, surface treatment agent, light-shielding solvent and water.

[0007] Among them, alumina flexible fibers are pure-phase alumina fibers with a hollow structure and a diameter of 100nm-10μm. They have the characteristics of ultra-lightness, good flexibility, thermal insulation, etc., and can improve the flexibility of ceramic-based aerogels.

[0008] The preparation method of alumina flexible fiber cites invention patent CN202211005924.1, specifically: S01: dissolving a water-soluble polymer in water to form a spinning aid solution; wherein the water-soluble polymer is one or more of polyethylene oxide PEO, polyvinyl pyrrolidone PVP, and polyvinyl alcohol PVA; S02: dissolving a water-soluble aluminum salt in deionized water to prepare a salt solution; wherein the water-soluble aluminum salt is one or more of aluminum chloride hexahydrate or aluminum nitrate; S03: slowly adding the salt solution to the spinning aid solution, placing it on a magnetic stirrer and stirring and mixing for 0.5h-10d to obtain a spinning precursor; wherein the mass of the water-soluble aluminum salt is 1-50 times the mass of the water-soluble polymer; S04: Add the spinning precursor into the syringe, extrude the spinning solution through the coaxial inner needle under the push of the mechanical pump, introduce gas through the coaxial outer needle, and form the spinning solution into drawn fiber under the action of the airflow; S05: The drawn fiber is heated to 180-400°C at a rate of 1-20°C / min in a muffle furnace, kept warm for 1-8h, and then heated to 600-1600°C at a rate of 1-20°C / min, kept warm for 2-8h to obtain alumina flexible fiber.

[0009] In the present application, the porous powder includes one or more of porous silicate powder, porous silicon powder, porous carbon powder and porous aluminum powder, and the particle size is 325-5000 mesh. The use of porous powder can reduce the thermal conductivity of ceramic-based aerogel and improve the thermal insulation effect.

[0010] The porous silicate powder includes 35-45% water glass, 35-45% solid silica gel, 15-25% sodium aluminate and 1-5% sodium hydroxide in terms of mass percentage. The porous silicate powder is prepared using water glass, solid silica gel and sodium aluminate as raw materials and sodium hydroxide as a catalyst. The specific preparation method includes: Dissolve water glass and solid silica gel in water respectively, stir evenly to form silica sol; dissolve sodium aluminate in water, stir evenly to form aluminum sol; mix silica sol, aluminum sol and sodium hydroxide evenly, stir in a constant temperature water bath at 25-35°C for 30 minutes to form a uniform silica-alumina gel. After aging the silica-alumina gel at 20°C for 20 hours, heat and crystallize at 100°C for 4 hours to obtain a crystallized product. The crystallized product is ultrasonically cleaned and centrifuged, washed until the pH of the supernatant is less than 9, and dried at 100°C for 4 hours to obtain a porous silicate powder.

[0011] The porous silicon powder comprises 69.5-79.5% silica sol, 20-30% potassium silicate and 0.5-3% potassium hydroxide in terms of mass percentage. The porous silicon powder is prepared with silica sol and potassium silicate as raw materials and potassium hydroxide as a catalyst. The specific preparation method includes: Dissolve silica sol in water and stir evenly to form a silica sol solution; dissolve potassium silicate in water and stir evenly to form potassium silicate sol; mix the silica sol solution, potassium silicate sol and potassium hydroxide evenly, and stir in a constant temperature water bath at 25-35°C for 30 minutes to form a uniform mixed sol. After aging the mixed sol at 60°C for 15 hours, heat and crystallize at 120°C for 2 hours to obtain a gel product. The gel product is placed in a microwave synthesizer and crystallized at a microwave radiation power of 100W, a wave radiation temperature of 120°C, and a microwave radiation time of 10 minutes to obtain a crystallized product. After cooling, the crystallized product is taken out, ultrasonically cleaned, centrifuged, washed until the pH of the supernatant is less than 9, and dried at 100°C for 4 hours to obtain a porous silicon powder.

[0012] The porous carbon powder includes 25-35% sodium carbonate, 60-70% sodium aluminate and 2-10% sodium hydroxide in terms of mass percentage. The porous carbon powder is prepared using sodium carbonate and sodium aluminate as raw materials and sodium hydroxide as a catalyst. The specific preparation method includes: Dissolve sodium carbonate in water and stir evenly to form a sodium carbonate solution; dissolve sodium aluminate in water and stir evenly to form an aluminum sol; mix the sodium carbonate solution, aluminum sol and sodium hydroxide evenly, and stir in a constant temperature water bath at 25-35°C for 30 minutes to form a uniform mixed sol. After aging the mixed sol at 40°C for 20 hours, heat and crystallize it at 90°C for 3 hours to obtain a gel product. The gel product is placed in a microwave synthesizer and crystallized under a microwave radiation power of 120W, a wave radiation temperature of 100°C, and a microwave radiation time of 15 minutes to obtain a crystallized product. After cooling, the crystallized product is taken out, ultrasonically cleaned, centrifuged, washed until the pH of the supernatant is less than 9, and dried at 100°C for 4 hours to obtain a porous carbon powder.

[0013] The porous aluminum powder includes 45-55% of neutral aluminum solution, 15-25% of water glass, 22-32% of sodium aluminate and 1-5% of sodium hydroxide in terms of mass percentage. The porous aluminum powder is prepared by using water glass, neutral aluminum sol and sodium aluminate as raw materials and sodium hydroxide as catalyst. The specific preparation method includes: Dissolve water glass in water and stir evenly to form silica sol; dissolve neutral aluminum sol and sodium aluminate in water respectively and stir evenly to form aluminum sol; mix silica sol, aluminum sol and sodium hydroxide evenly and stir in a constant temperature water bath at 25-35°C for 30 minutes to form a uniform silica-alumina gel. After aging the silica-alumina gel at 60°C for 16 hours, heat and crystallize at 130°C for 1 hour to obtain a crystallized product. The crystallized product is ultrasonically cleaned and centrifuged, washed until the pH of the supernatant is less than 9, and dried at 100°C for 4 hours to obtain a porous aluminum powder.

[0014] In the present application, the sol includes one or more of methanol, ethanol and butanol; the cross-linking agent is one or more of tetraethyl orthosilicate and trimethoxysilane; the catalyst is tributylaluminum oxide; the solid content of the silica aqueous solution is 2-20%; the surface treatment agent is the WP001 mixed liquid with batch number 20250215006 produced by Nanjing Qinghai Trading Co., Ltd.; the shading solvent includes one or more of tetrabutyl titanate, isopropyl titanate and titanium dioxide sol.

[0015] In the present application, the raw materials for preparing ceramic-based aerogel include, by weight: 15-40 parts of alumina flexible fibers, 2-20 parts of porous powder, 0.5-5 parts of sol, 0.2-3 parts of cross-linking agent, 0.5-10 parts of catalyst, 400-2000 parts of silica aqueous solution, 5-20 parts of surface treatment agent, 100-1500 parts of shading solvent and 1000-3500 parts of water.

[0016] The present application provides a method for preparing a ceramic-based aerogel, the method comprising: S01: After mixing alumina flexible fibers, porous powder, sol, cross-linking agent, catalyst and water, fiber gel is synthesized by in-situ generation method under the conditions of 90-250°C and 0.1-3MPa.

[0017] Alumina flexible fibers, porous powder, sol, crosslinking agent, catalyst and water are mixed, and at a specific temperature and pressure of 90-250°C and 0.1-3MPa, the alumina flexible fibers, porous powder and crosslinking agent react physically and chemically under the action of the catalyst to generate thermodynamically stable fiber gel. In the present application, the reaction temperature and pressure are specific, and the reaction of alumina flexible fibers and porous powder cannot be induced if it is not at this temperature and pressure.

[0018] S02: After the fiber gel is soaked in the silica aqueous solution, it is dried at 180-250° C. to form a hard fiber gel.

[0019] The fiber gel is soaked in the silica aqueous solution for 20-30 minutes to allow the silica aqueous solution to completely penetrate the fiber gel. After soaking, the fiber gel is placed in a drying furnace and dried at 180-250°C to allow the silica to undergo a ceramic reaction, thereby generating a hard fiber gel with a harder material, thereby achieving the purpose of enhancing the structural strength of the ceramic-based aerogel.

[0020] In the present application, the fiber gel soaked in the silica aqueous solution must be dried at 180-250°C. If the temperature is lower than 180°C, the silica will not undergo a ceramic reaction and the surface of the fiber gel will not harden. If the temperature is higher than 250°C, the energy consumption is high, resulting in a higher preparation cost.

[0021] S03: After the hard fiber gel is soaked in the surface treatment agent, it is dried by microwave at 60-180° C. to form a waterproof fiber gel.

[0022] The hard fiber gel is soaked in the surface treatment agent for 10-15 minutes to allow the surface treatment agent to penetrate into the surface of the hard fiber gel. After soaking, the hard fiber gel is dried in a microwave environment at 60-180°C to evaporate the solvent on the surface of the hard fiber gel, so that the surface treatment agent is solidified on the surface of the hard fiber gel to form a waterproof fiber gel.

[0023] In the present application, microwave heating is used to dry the hard fiber gel, which has the advantages of short drying time and high efficiency.

[0024] S04: After the surface of the waterproof fiber gel is evenly sprayed with a light-shielding solvent, infrared drying is performed at 80-120° C. to obtain a ceramic-based aerogel.

[0025] The present invention has the following beneficial effects: (1) The ceramic-based aerogel is made of hollow structure, flexible alumina fibers and porous powder as the main raw materials. It can generate fiber gel in situ under the action of catalyst, which improves the flexibility of the ceramic-based aerogel and greatly reduces the thermal conductivity, making the ceramic-based aerogel have good heat absorption effect and excellent fireproof and heat-insulating properties. In the low-temperature field, the thermal insulation effect is equivalent to that of glass fiber aerogel, and in the high-temperature field, the thermal insulation effect is better than that of ceramic aerogel.

[0026] (2) The synergistic effect of alumina flexible fibers and silica aqueous solution can enhance the mechanical strength and flexibility of ceramic-based aerogels and improve their mechanical capabilities.

[0027] (3) The use of surface treatment agent can make ceramic-based aerogel have good waterproof ability. The synergistic effect of low thermal conductivity alumina flexible fiber and shading solvent can make ceramic-based aerogel have better heat absorption effect and excellent fireproof and heat-insulating properties.

[0028] (4) The preparation method has simple process, low cost and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a microscope inspection image of the ceramic-based aerogel prepared in the embodiment of the present application; Figure 2 This is a sample comparison diagram of the ceramic-based aerogel, glass fiber aerogel and ceramic aerogel prepared in Example 6 of the present application after the back temperature experiment is completed; Figure 3 This is a diagram of the waterproofing experiment of the ceramic-based aerogel prepared in Example 6 of the present application. DETAILED DESCRIPTION

[0030] The technical solution of the present invention is further explained and illustrated by means of specific embodiments below.

[0031] Example 1 The embodiment of the present application provides a ceramic-based aerogel, and the raw materials for its preparation include, in parts by weight: 30 parts of alumina flexible fibers, 4 parts of porous silicate powder, 0.6 parts of methanol, 0.8 parts of tetraethyl orthosilicate, 0.5 parts of tributyl aluminum oxide, 1000 parts of silica aqueous solution, 8 parts of WP001 mixed solution, 300 parts of tetrabutyl titanate and 3000 parts of water.

[0032] The preparation method of the ceramic-based aerogel comprises: S101: Alumina flexible fibers, porous silicate powder, methanol, tetraethyl orthosilicate, tributylaluminum oxide and water are mixed, and fiber gel is synthesized by an in-situ generation method at 90° C. and 0.5 MPa.

[0033] S102: Soak the fiber gel in a silica aqueous solution for 20 minutes. After soaking, place the fiber gel in a drying furnace and dry it at 180° C. to form a hard fiber gel.

[0034] S103: soaking the hard fiber gel in the WP001 mixed solution for 10 minutes. After soaking, drying the hard fiber gel in a microwave environment at 80° C. to form a waterproof fiber gel.

[0035] S104: After evenly spraying tetrabutyl titanate on the surface of the waterproof fiber gel, infrared drying is performed at 120° C. to obtain a ceramic-based aerogel.

[0036] Example 2 The embodiment of the present application provides a ceramic-based aerogel, and the raw materials for its preparation include, in parts by weight: 25 parts of alumina flexible fibers, 6 parts of porous silicon powder, 1.5 parts of ethanol, 0.5 parts of trimethoxysilane, 4 parts of tributyl aluminum oxide, 500 parts of silica aqueous solution, 5 parts of WP001 mixed solution, 1200 parts of isopropyl titanate and 2500 parts of water.

[0037] The preparation method of the ceramic-based aerogel comprises: S201: Alumina flexible fibers, porous silicon powder, ethanol, trimethoxysilane, tributylaluminum oxide and water are mixed, and fiber gel is synthesized by an in-situ generation method at 150° C. and 0.8 MPa.

[0038] S202: Soak the fiber gel in a silica aqueous solution for 30 minutes. After soaking, place the fiber gel in a drying furnace and dry it at 180° C. to form a hard fiber gel.

[0039] S203: soaking the hard fiber gel in the WP001 mixed solution for 15 minutes. After soaking, drying the hard fiber gel in a microwave environment at 180° C. to form a waterproof fiber gel.

[0040] S204: After isopropyl titanate is uniformly sprayed on the surface of the waterproof fiber gel, infrared drying is performed at 110° C. to obtain a ceramic-based aerogel.

[0041] Example 3 The embodiment of the present application provides a ceramic-based aerogel, and the raw materials for its preparation include, in parts by weight: 20 parts of alumina flexible fibers, 15 parts of porous aluminum powder, 0.4 parts of methanol, 0.5 parts of butanol, 1.5 parts of trimethoxysilane, 1 part of tributylaluminum oxide, 2000 parts of silica aqueous solution, 10 parts of WP001 mixed solution, 500 parts of titanium dichloride sol and 2000 parts of water.

[0042] The preparation method of the ceramic-based aerogel comprises: S301: Alumina flexible fibers, porous aluminum powder, methanol, butanol, trimethoxysilane, tributylaluminum oxide and water are mixed, and fiber gel is synthesized by an in-situ generation method at 100°C and 1MPa.

[0043] S302: Soak the fiber gel in a silica aqueous solution for 25 minutes. After soaking, place the fiber gel in a drying furnace and dry it at 180° C. to form a hard fiber gel.

[0044] S303: soaking the hard fiber gel in the WP001 mixed solution for 12 minutes. After soaking, drying the hard fiber gel in a microwave environment at 80° C. to form a waterproof fiber gel.

[0045] S304: After uniformly spraying titanium dichloride sol on the surface of the waterproof fiber gel, infrared drying at 80° C. is performed to obtain a ceramic-based aerogel.

[0046] Example 4 The embodiment of the present application provides a ceramic-based aerogel, and the raw materials for its preparation include, in parts by weight: 35 parts of alumina flexible fibers, 4 parts of porous silicate powder, 6 parts of porous silicon powder, 3 parts of butanol, 2 parts of tetraethyl orthosilicate, 2 parts of tributyl aluminum oxide, 800 parts of silica aqueous solution, 10 parts of WP001 mixed solution, 700 parts of tetrabutyl titanate, 600 parts of isopropyl titanate and 3500 parts of water.

[0047] The preparation method of the ceramic-based aerogel comprises: S401: Alumina flexible fibers, porous silicate powder, porous silicon powder, butanol, ethyl orthosilicate, tributylaluminum oxide and water are mixed, and fiber gel is synthesized by in-situ generation method at 250° C. and 3 MPa.

[0048] S402: Soak the fiber gel in a silica aqueous solution for 25 minutes. After soaking, place the fiber gel in a drying furnace and dry it at 180° C. to form a hard fiber gel.

[0049] S403: soaking the hard fiber gel in the WP001 mixed solution for 10 minutes. After soaking, drying the hard fiber gel in a microwave environment at 150° C. to form a waterproof fiber gel.

[0050] S404: After evenly spraying tetrabutyl titanate and isopropyl titanate on the surface of the waterproof fiber gel, infrared drying is performed at 120° C. to obtain a ceramic-based aerogel.

[0051] Example 5 The embodiment of the present application provides a ceramic-based aerogel, and the raw materials for its preparation include, in parts by weight: 15 parts of alumina flexible fibers, 5 parts of porous silicate powder, 10 parts of porous aluminum powder, 4 parts of ethanol, 0.8 parts of tetraethyl orthosilicate, 0.2 parts of trimethoxysilane, 8 parts of tributyl aluminum oxide, 600 parts of silica aqueous solution, 15 parts of WP001 mixed solution, 800 parts of isopropyl titanate and 1500 parts of water.

[0052] The preparation method of the ceramic-based aerogel comprises: S501: Alumina flexible fibers, porous silicate powder, porous aluminum powder, ethanol, tetraethyl orthosilicate, trimethoxysilane, tributylaluminum oxide and water are mixed, and fiber gel is synthesized by an in-situ generation method at 150° C. and 1.5 MPa.

[0053] S502: Soak the fiber gel in a silica aqueous solution for 20 minutes. After soaking, place the fiber gel in a drying furnace and dry it at 250° C. to form a hard fiber gel.

[0054] S503: soaking the hard fiber gel in the WP001 mixed solution for 10 minutes. After soaking, drying the hard fiber gel in a microwave environment at 100° C. to form a waterproof fiber gel.

[0055] S504: After isopropyl titanate is uniformly sprayed on the surface of the waterproof fiber gel, infrared drying is performed at 100° C. to obtain a ceramic-based aerogel.

[0056] Example 6 The embodiment of the present application provides a ceramic-based aerogel, and the raw materials for its preparation include, in parts by weight: 20 parts of alumina flexible fibers, 3 parts of porous silicon powder, 3 parts of porous aluminum powder, 2 parts of porous carbon powder, 0.4 parts of methanol, 0.5 parts of butanol, 1 part of trimethoxysilane, 3 parts of tributyl aluminum oxide, 1500 parts of silica aqueous solution, 10 parts of WP001 mixed solution, 500 parts of isopropyl titanate and 2000 parts of water.

[0057] The preparation method of the ceramic-based aerogel comprises: S601: Alumina flexible fibers, porous silicon powder, porous aluminum powder, porous carbon powder, methanol, butanol, trimethoxysilane, tributylaluminum oxide and water are mixed, and fiber gel is synthesized by in-situ generation method at 200°C and 2MPa.

[0058] S602: Soak the fiber gel in a silica aqueous solution for 30 minutes. After soaking, place the fiber gel in a drying furnace and dry it at 180° C. to form a hard fiber gel.

[0059] S603: soaking the hard fiber gel in the WP001 mixed solution for 10 minutes. After soaking, drying the hard fiber gel in a microwave environment at 120° C. to form a waterproof fiber gel.

[0060] S604: After isopropyl titanate is uniformly sprayed on the surface of the waterproof fiber gel, infrared drying is performed at 80° C. to obtain a ceramic-based aerogel.

[0061] Example 7 The embodiment of the present application provides a ceramic-based aerogel, and the raw materials for its preparation include, in parts by weight: 10 parts of alumina flexible fibers, 6 parts of porous silicate powder, 8 parts of porous carbon powder, 0.3 parts of methanol, 2 parts of ethanol, 2 parts of tetraethyl orthosilicate, 1 part of trimethoxysilane, 2 parts of tributylaluminum oxide, 1500 parts of silica aqueous solution, 20 parts of WP001 mixed solution, 300 parts of tetrabutyl titanate, 300 parts of titanium dioxide sol and 1000 parts of water.

[0062] The preparation method of the ceramic-based aerogel comprises: S701: Alumina flexible fibers, porous silicate powder, porous carbon powder, methanol, ethanol, tetraethyl orthosilicate, trimethoxysilane, tributylaluminum oxide and water are mixed, and fiber gel is synthesized by in-situ generation method at 170°C and 2.5MPa.

[0063] S702: Soak the fiber gel in a silica aqueous solution for 25 minutes. After soaking, place the fiber gel in a drying furnace and dry it at 200° C. to form a hard fiber gel.

[0064] S703: Soak the hard fiber gel in the WP001 mixed solution for 13 minutes. After soaking, dry the hard fiber gel in a microwave environment at 100° C. to form a waterproof fiber gel.

[0065] S704: After evenly spraying tetrabutyl titanate and titanium dioxide sol on the surface of the waterproof fiber gel, infrared drying at 90° C. is performed to obtain a ceramic-based aerogel.

[0066] Example 8 The embodiment of the present application provides a ceramic-based aerogel, and the raw materials for its preparation include, in parts by weight: 25 parts of alumina flexible fibers, 3 parts of porous silicate powders, 3 parts of porous silicon powders, 2 parts of porous carbon powders, 5 parts of ethanol, 1 part of tetraethyl orthosilicate, 3 parts of tributyl aluminum oxide, 1300 parts of silica aqueous solution, 10 parts of WP001 mixed solution, 1500 parts of isopropyl titanate and 2500 parts of water.

[0067] The preparation method of the ceramic-based aerogel comprises: S801: Alumina flexible fibers, porous silicate powder, porous silicon powder, porous carbon powder, ethanol, tetraethyl orthosilicate, tributylaluminum oxide and water are mixed, and fiber gel is synthesized by in-situ generation method at 140°C and 1.5MPa.

[0068] S802: Soak the fiber gel in a silica aqueous solution for 20 minutes. After soaking, place the fiber gel in a drying oven and dry it at 180° C. to form a hard fiber gel.

[0069] S803: Soak the hard fiber gel in the WP001 mixed solution for 15 minutes. After soaking, dry the hard fiber gel in a microwave environment at 120° C. to form a waterproof fiber gel.

[0070] S804: After uniformly spraying isopropyl titanate on the surface of the waterproof fiber gel, infrared drying is performed at 80° C. to obtain a ceramic-based aerogel.

[0071] The ceramic-based aerogel prepared in Example 6 of the present application was examined under a microscope, and the attached Figure 1 . Figure 1 It can be seen that in the ceramic-based aerogel prepared in Example 6 of the present application, the slender structure is alumina flexible fibers, and the surface of the fibers is loaded with black and white granular porous powders or porous powders with larger particle sizes caused by agglomeration.

[0072] The commercially available glass fiber aerogel was used as comparative example 1, the commercially available ceramic aerogel was used as comparative example 2, and the ceramic-based aerogel prepared in Example 6 of the present application was tested for hardness, thermal conductivity, back temperature and waterproof performance, and the specific contents are as follows: 1. Hardness test The hardness of the aerogels in Example 6, Comparative Example 1 and Comparative Example 2 was tested using an LX-A Shore hardness tester. The test results are shown in Table 1.

[0073] Table 1: Hardness test data of aerogels in Example 6, Comparative Example 1 and Comparative Example 2 As can be seen from Table 1, the hardness of the commercially available ceramic aerogel in Comparative Example 2 is relatively poor, while the ceramic-based aerogel in Example 6 of the present application and the commercially available glass fiber aerogel in Comparative Example 1 have relatively high hardness, which is convenient for transportation and construction.

[0074] 2. Thermal conductivity test The thermal conductivity of the aerogels in Example 6, Comparative Example 1 and Comparative Example 2 was tested at 100°C, 300°C, 500°C, 700°C and 900°C, respectively. The test results are shown in Table 2.

[0075] Table 2: Thermal conductivity test data of aerogels in Example 6, Comparative Example 1 and Comparative Example 2 As can be seen from Table 2, at different test temperatures, the thermal conductivity of the glass fiber aerogel in Comparative Example 1 is relatively small at low temperatures, and when the temperature exceeds 600°C, the temperature resistance limit of the glass fiber aerogel is reached; as the temperature continues to rise, the thermal conductivity increases significantly, and the rate of increase is particularly fast. The thermal conductivity of the ceramic aerogel in Comparative Example 2 is relatively large at low temperatures, and as the temperature increases, the rate of increase of the thermal conductivity is relatively low, and the thermal conductivity advantage becomes more and more obvious. The thermal conductivity of the ceramic-based aerogel in Example 6 of the present application is relatively small at low temperatures, which is basically the same as that of Comparative Example 1; as the temperature continues to rise, the rate of increase of the thermal conductivity is relatively low, and the thermal conductivity at the same temperature is lower than that in Comparative Example 2. It can be seen that the ceramic-based aerogel prepared in the embodiment of the present application has a low thermal conductivity at both low and high temperatures, which is beneficial to the thermal insulation performance of the product.

[0076] 3. Back temperature detection The aerogels in Example 6, Comparative Example 1 and Comparative Example 2 of the same thickness were taken and irradiated with a spray gun at a temperature of 1100°C. The back temperature of each group was tested at 0min, 1min, 3min, 5min, 7min and 9min respectively. The test results are shown in Table 3. The comparison diagram of the samples after the back temperature test is shown in Table 3. Figure 2 shown.

[0077] Table 3: Back temperature detection data of aerogels in Example 6, Comparative Example 1 and Comparative Example 2 As can be seen from Table 3, under the irradiation of a spray gun at a temperature of 1100°C, the glass fiber aerogel in Comparative Example 1 was directly burned through in less than 1 minute of irradiation. In different time periods, the back temperature of the ceramic aerogel in Example 6 is lower than the back temperature of the ceramic aerogel in Comparative Example 2. This is because the glass fiber aerogel in Comparative Example 1 is composed of glass fibers. When the temperature exceeds 600°C, the glass fibers will melt and be burned through. The ceramic-based aerogel in Example 6 of the present application has a lower thermal conductivity. Under the synergistic effect of the high-temperature radiation sunshade, the back temperature of the ceramic-based aerogel is lower than the back temperature of the ceramic aerogel in Comparative Example 2.

[0078] In addition, by the attached Figure 2 It can be seen that the glass fiber aerogel sample in Comparative Example 1 has been burned through; the ceramic aerogel sample in Comparative Example 2 is bent, which indicates that its structural strength is poor; and the ceramic-based aerogel sample in Example 6 of the present application is in good condition.

[0079] 4. Waterproof performance test Water was dripped onto the aerogel samples in Example 6, Comparative Example 1, and Comparative Example 2 using a dropper. After standing for 24 hours, the water absorption rate of each group was measured. The test results are shown in Table 4. The waterproof test diagram of the ceramic-based aerogel in Example 6 is shown in the attached figure. Figure 3 shown.

[0080] Table 4: Water absorption test data of aerogels in Example 6, Comparative Example 1 and Comparative Example 2 From Table 4 and Appendix Figure 3 It can be seen that the aerogels in Example 6, Comparative Example 1 and Comparative Example 2 all have good waterproof properties.

[0081] Through the above tests, it can be seen that compared with glass fiber aerogel and ceramic aerogel, the ceramic-based aerogel prepared in the embodiment of the present application has higher hardness, lower thermal conductivity, back temperature and water absorption, which can not only achieve the purpose of fire prevention and heat insulation, but also has good waterproof performance.

[0082] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A ceramic-based aerogel, characterized in that: The preparation raw materials include: flexible alumina fiber, porous powder, sol, crosslinking agent, catalyst, silica aqueous solution, surface treatment agent, shading solvent and water, wherein the flexible alumina fiber is a pure phase alumina fiber with a hollow structure and a diameter of 100nm-10μm.

2. The ceramic-based aerogel according to claim 1, characterized in that: The raw materials for preparation include, by weight: 15-40 parts of alumina flexible fibers, 2-20 parts of porous powder, 0.5-5 parts of sol, 0.2-3 parts of crosslinking agent, 0.5-10 parts of catalyst, 400-2000 parts of silica aqueous solution, 5-20 parts of surface treatment agent, 100-1500 parts of shading solvent and 1000-3500 parts of water.

3. The ceramic-based aerogel according to claim 1, characterized in that: The porous powder includes one or more of porous silicate powder, porous silicon powder, porous carbon powder and porous aluminum powder.

4. The ceramic-based aerogel according to claim 3, characterized in that: The porous silicate powder comprises 35-45% water glass, 35-45% solid silica gel, 15-25% sodium aluminate and 1-5% sodium hydroxide in terms of mass percentage.

5. The ceramic-based aerogel according to claim 3, characterized in that: The porous silicon-based powder comprises 69.5-79.5% of silica sol, 20-30% of potassium silicate and 0.5-3% of potassium hydroxide in terms of mass percentage.

6. The ceramic-based aerogel according to claim 3, characterized in that: The porous carbon powder comprises 25-35% sodium carbonate, 60-70% sodium aluminate and 2-10% sodium hydroxide in terms of mass percentage.

7. The ceramic-based aerogel according to claim 3, characterized in that: The porous aluminum powder comprises, by mass percentage, 45-55% of a neutral aluminum solution, 15-25% of water glass, 22-32% of sodium aluminate and 1-5% of sodium hydroxide.

8. The ceramic-based aerogel according to claim 1, characterized in that: The sol includes one or more of methanol, ethanol and butanol, and the cross-linking agent is one or more of ethyl orthosilicate and trimethoxysilane.

9. The ceramic-based aerogel according to claim 1, characterized in that: The catalyst is tributyl aluminum oxide, the surface treatment agent is WP001 mixed solution, and the light-shielding solvent includes one or more of tetrabutyl titanate, isopropyl titanate and titanium dioxide sol.

10. A method for preparing a ceramic-based aerogel according to any one of claims 1 to 9, characterized in that: include: After mixing alumina flexible fibers, porous powder, sol, crosslinking agent, catalyst and water, the fiber gel is synthesized by an in-situ generation method at 90-250° C. and 0.1-3 MPa; After the fiber gel is soaked in the silica aqueous solution, it is dried at 180-250° C. to form a hard fiber gel; After the hard fiber gel is soaked in the surface treatment agent, it is dried by microwave at 60-180° C. to form a waterproof fiber gel; After the surface of the waterproof fiber gel is uniformly sprayed with a light-shielding solvent, infrared drying at 80-120° C. is performed to obtain a ceramic-based aerogel.

Citation Information

Patent Citations

  • A kind of alumina flexible fiber and preparation method thereof

    CN115262032B

  • Method for preparing heat-resisting alumina-silox aerogel thermal-protective composite material

    CN101792299A

  • Foamed ceramic reinforcing fiber aerogel insulating material and preparation method thereof

    CN101913835A

  • In-situ composite silicon-based multibasic oxide oxide aerogel material and preparation method thereof

    CN104941538A

  • Aerogel modified glass fiber insulation board and preparation method thereof

    CN114634331A